Turning the tide: a 2°C increase in heat tolerance can halve climate change‐induced losses in four cold‐adapted kelp species - Hill, Griffin (2025)
Kelp forests are susceptible to climate change, as their sessile nature and low dispersal capacity hinder tracking of suitable conditions. The emergence of a wide array of approaches to increasing thermal tolerance seeks to change the outlook of biodiversity in a changing climate but lacks clear targets of impactful thermal resilience. Here, we utilize species distribution models (SDMs) to evaluate the potential of enhanced thermal tolerance to buffer the effects of climate change on cold-adapted kelp species: Saccharina latissima, Alaria esculenta, Laminaria hyperborea, and Laminaria digitata. For each species, we compared a baseline model-where the thermal niche remained unchanged-to models where the simulated maximum sea surface temperature tolerance was increased by 1 degrees C-5 degrees C. These models were projected into three climate change scenarios: sustainability (Shared Socioeconomic Pathway (SSP) 1-1.9, Paris Agreement), regional rivalry (SSP3-7.0), and fossil-fuel development (SSP 5-8.5). Our SDMs demonstrate that an increase of 1 degrees C-2 degrees C in thermal tolerance could recover over 50% of predicted losses of suitable habitat for cold-adapted kelps. However, A. esculenta, a species of growing commercial interest, still faced persistent habitat contraction across all climate change scenarios and simulated tolerance increases, including up to 15% unrecovered losses under SSP5-8.5, even with a simulated 5 degrees C increase in thermal tolerance. Our findings highlight the need for a two-pronged approach to conserve cold-adapted kelp forests: stringent reductions in greenhouse gas emission reductions in line with the SSP1-1.9 scenario, and strategies to boost kelp's thermal tolerance by at least 1 degrees C-2 degrees C. This dual approach is crucial to maintain 90% of the current suitable habitat of S. latissima and L. digitata, and 70% for A. esculenta and L. hyperborea. Relying on mitigation or adaptation alone will likely be insufficient to maintain their historic range under projected climate change.